Kaderisasi Mahasiswa Keuskupan Surabaya dalam Terang Seruan Apostolik Christus Vivit - Widyawan Louis, Aloysius (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2023)
The Surabaya Diocese Students Cadreization Program (Program Kaderisasi Mahasiswa Keuskupan Surabaya) is a response to the Church's solicitude for the condition of Catholic students who need to apprehend and face the challenges of the times in the light of their creed. In a particular way, this program focuses on cultivating the Church cadres who are discerning, reflective, perceptive, and in solidarity with all the problems of life around them, both on their campus and in their community, based on the spirituality and values of the Catholic Social Teachings. During the evaluation and reflection process of the program, which has been ongoing for five years (2019-2023), the team of facilitators came across Pope Francis' Apostolic Exhortation entitled “Christus Vivit” which was promulgated on March 25, 2019. In this document, the Pope listens to young Catholics throughout the world, draws inspiration from sources of faith, and sets the basic guidance for the integral formation of the Catholic youth that should always be contextual to the current times. This article provides a clear reflection on The Surabaya Diocese Students Cadreization Program (Program Kaderisasi Mahasiswa Keuskupan Surabaya) in light of the spirit and values called for by Pope Francis in